On a fractional integro-differential inclusion - Aurelian Cernea (Electronic Journal of Qualitative Theory of Differential Equations, 2014)
We study a Cauchy problem for a fractional integro-differential inclusion of order $α \in (1,2]$ involving a nonconvex set-valued map. Arcwise connectedness of the solution set is provided. Also we prove that the set of selections corresponding to the solutions of the problem considered is a retract of the space of integrable functions on a given interval.